Exploring the impact of teaching virtual museum design on undergraduate art students' interest and perception of museums - Xu, Zixin; Dahlan, Nur Dalilah; Lin, Jing; Syed Abdullahe, Sharifah Intan Sharina; Sahrir, Syazwani (IEEE, 2023)
Virtual museums have gained popularity due to their interactive and immersive media experiences and have been used to train technical staff and develop design strategies. They present unique challenges for traditional museums, especially when attracting younger audiences. To engage younger visitors, museums must innovate and improve their offerings by providing opportunities for active engagement and immersive cultural experiences. Research has shown that teaching virtual museum design to art students positively impacts their perceptions of museums and increases their interest. This thesis aims to design an effective virtual museum design course using the ADDIE model for undergraduate art students, focusing on the creation of virtual museums using the Unity3D engine, and exploring the potential of virtual museums to enhance young people’s attitudes towards museum visits.